Mobile late endosomes modulate peripheral endoplasmic reticulum network architecture. (8th February 2021) - Spits, Menno; Heesterbeek, Iris T; Voortman, Lennard M; Akkermans, Jimmy J; Wijdeven, Ruud H; Cabukusta, Birol; Neefjes, Jacques
Abstract: The endoplasmic reticulum (ER) is the largest organelle contacting virtually every other organelle for information exchange and control of processes such as transport, fusion, and fission. Here, we studied the role of the other organelles on ER network architecture in the cell periphery. We show that the co‐migration of the ER with other organelles, called ER hitchhiking facilitated by late endosomes and lysosomes is a major mechanism controlling ER network architecture. When hitchhiking occurs, emerging ER structures may fuse with the existing ER tubules to alter the local ER architecture. This couples late endosomal/lysosomal positioning and mobility to ER network architecture. Conditions restricting late endosomal movement—including cell starvation—or the depletion of tether proteins that link the ER to late endosomes reduce ER dynamics and limit the complexity of the peripheral ER network architecture. This indicates that among many factors, the ER is controlled by late endosomal movement resulting in an alteration of the ER network architecture. SYNOPSIS: The endoplasmic reticulum (ER) co‐migrates or " hitchhikes " with the RAB7‐positive late endosomes/lysosomes in a membrane contact site‐mediated manner to determine the architecture of the peripheral ER network. Factors controlling late endosomal movement such as starvation affect ER network architecture. ER hitchhiking with late endosomes/lysosomes determines the ER network structure and complexity. The hitchhiking of the ER relies on the ER‐resident membrane contact site proteins. Limiting peripheral movement of late endosomes by RAB7‐effector RILP alters the peripheral ER network. Starvation sensed by TMEM55B restricts late endosomal movement resulting in a more open peripheral ER network. Abstract : The endoplasmic reticulum co‐migrates or " hitchhikes " with the RAB7‐positive late endosomes/lysosomes in a membrane contact site‐mediated manner to determine the architecture of the peripheral ER network.